Conservation tillage improves productivity of sunflower (Helianthus annuus L.) under reduced irrigation on sandy loam soil. - Ahmad Sher; Muhammad Yasir Arfat; Sami Ul-Allah; Abdul Sattar; Muhammad Ijaz; Abdul Manaf; Abdul Qayyum; Ali Tan Kee Zuan; Omaima Nasif; Kristina Gasparovic (PLoS ONE)
Sunflower production is significantly lower in arid and semi-arid regions due to various crop management problem. Conservation of tillage provides the most excellent opportunity to reduce degradation of soil reserves and increase soil productivity. The main objective of this study was to investigate the combined effects of conservation tillage and drought stress on growth and productivity of different sunflower hybrids. Experimental treatments included two sunflower hybrids ('NK-Senji' and 'S-278'), two drought stress treatments (i.e., well-watered and drought stress at flowering and grain filling stages) and three tillage practices (i.e., conservation, minimum and deep tillage). The results indicated that morphological and physiological parameters, and yield-related traits were significantly (P≤0.05) affected by all individual factors; however, their interactive effects were non-significant. Among sunflower hybrids, 'NK-Senji' performed better for morphological, physiological, and yield-related traits than 'S-278'. Similarly, conservation tillage observed better traits compared to the rest of the tillage practices included in the study. Nonetheless, conservation tillage improved growth and yield-related traits of hybrid 'NK-Senji' under drought stress. Hence, it is concluded that conservation tillage can improve the productivity of sunflower under low moisture availability. Therefore, conservation tillage could be suggested in the areas of lower water ability to improve sunflower production. Nonetheless, sunflower hybrids or varieties need thorough testing for their adaptability to conservation tillage and low moisture availability before making recommendations.